Preoperative Decolonization Appears to Reduce the Risk of Infection in High-Risk Groups Undergoing Total Hip Arthroplasty - Markus Scharf; Dominik Emanuel Holzapfel; Marianne Ehrnsperger; Joachim Grifka (MDPI AG, 2023)
Background: Periprosthetic infections represent a major challenge for doctors and patients. The aim of this study was therefore to determine whether the risk of infection can be positively influenced by preoperative decolonization of the skin and mucous membranes. Methods: In a retrospective analysis of 3082 patients who had undergone THA between 2014 and 2020, preoperative decolonization with octenidine dihydrochlorid was performed in the intervention group. In an interval of 30 days, soft tissue and prosthesis infections were detected, and an evaluation between the study groups was made by using a bilateral t-test regarding the presence of an early infection. The study groups were identical with regard to the ASA score, comorbidities, and risk factors. Results: Patients treated preoperatively with the octenidine dihydrochloride protocol showed lower early infection rates. In the group of intermediate- and high-risk patients (ASA 3 and higher), there was generally a significantly increased risk. The risk of wound or joint infection within 30 days was 1.99% higher for patients with ASA 3 or higher than for patients with standard care (4.11% [13/316] vs. 2.02% [10/494]; p = 0.08, relative risk 2.03). Preoperative decolonization shows no effect on the risk of infection that increases with age, and a gender-specific effect could not be detected. Looking at the body mass index, it could be shown that sacropenia or obesity leads to increased infection rates. Preoperative decolonization led to lower infection rates in percentage terms, which, however, did not prove to be significant (BMI < 20 1.98% [5/252] vs. 1.31% [5/382], relative risk 1.43, BMI > 30 2.58% [5/194] vs. 1.20% [4/334], relative risk 2.15). In the spectrum of patients with diabetes, it could be shown that preoperative decolonization leads to a significantly lower risk of infection (infections without protocol 18.3% (15/82), infections with protocol 8.50% (13/153), relative risk 2.15, p = 0.04. Conclusion: Preoperative decolonization appears to show a benefit, especially for the high-risk groups, despite the fact that in this patient group there is a high potential for resulting complications.